Uncertainty Amidst Routineness: How Three Lung Cancer Patients Experienced Alienation in Biomedical Institutions and Personal Relationships. - Coopersmith, Ari (Tidsskrift for Forskning i Sygdom og Samfund, 2018)
Anthropological and clinical research has brought to light emotionally isolating effects of receiving biomedical treatment for serious illnesses such as lung cancer. This essay illustrates how these isolating effects can manifest for individuals by presenting the experiences of three lung cancer patients in England who were interviewed between 2000 and 2003. The patients discussed feeling emotionally alienated in medical contexts because their illnesses tended to be routinely encountered by their caregivers, yet new and frightening for themselves. They stressed the importance of meaningful relationships with individual care providers in mitigating these alienating effects. They also discussed tensions between the emotional support provided by family and friends, and difficulty when the same loved ones could not fully understand their illness experiences. I conclude that in biomedical institutions and society as a whole, greater attention should be paid to patients’ feelings of isolation and alienation, and that the root causes of these experiences should be examined at institutional and societal levels.